Design and Performance Test of Specific Primers to Detect Bovine DNA Fragments using Multiplex PCR Technique for Halal Authentification - Kusnadi, Joni; Hernandi, Kevin Hohn; Al-Awwaly, Khotibul Umam; Arumingtyas, Estri Laras; Hakiki, Hilda Maghfirotu; Istianah, Nur (Indonesian Journal of Halal Research, 2022)
Adulterating meat products with several species, including non-halal species, is often found in commercial products. This study aims to design and validate the Cytochrome c oxidase subunit I (CO1) primers to detect the non-halal species. A pair of species-specific primers encoding the CO1 gene were designed to amplify bovine DNA, tested for specificity, and applied in multiplex polymerase chain reaction (PCR) technique with D-loop primers for pigs, Cyt-b for rats, and 12S rRNA for dogs. The CO1 primers, along with D-loop primers for porcine, Cyt-b primers for rats, and 12S rRNA primers for dogs can be used to detect specific bovine DNA with a size of 279 bp and sequence similarity of 96%. In addition, dog, rat, and porcine DNA were amplified at 101, 603, and 951 bp, respectively. These four primers are specific and can amplify the target DNA to detect non-halal meat component contamination in a single reaction process.